Pyramid of argumentation: towards an integrated model for teaching and assessing ESL writing - Nimehchisalem, Vahid (Universiti Putra Malaysia Press, 2018)
In an argumentative piece of writing, an issue is put forth, its pros and cons are considered, and the writer’s justification(s) for supporting one of them is presented. Although there are several models of argumentation, what is lacking in the literature is a comprehensive model for assessing writing by English as a Second Language (ESL) learners. This paper presents the Pyramid of Argumentation (PoA) that is an integrated model for assessing writing. As a three-sided pyramid standing on four columns, PoA integrates several recent and ancient theories of argumentation, linguistic competence, and language assessment. While the pyramid focuses on the components of argumentative writing, the pillars involve components of language ability and language assessment. The four sides of the pyramid, logos, ethos, rhetorical situation, as well as style and arrangement represent adapted version of the Classical Rhetoric as re-introduced by Crowley (1994) and Kinneavy (1971). The side of the pyramid that covers logos is replaced by Toulmin’s (2003) Model of Argument. The four columns, on which the pyramid is based, include the language knowledge, context of situation, world knowledge, and strategic knowledge. PoA integrates the theory of Communicative Language Ability (Bachman, 1990) with Components of Language Competence (Bachman, 1990). Writing teachers and material developers can use the PoA to make sure that they cover all the skills that learners need to develop mature pieces of argumentative writing. With the PoA as a framework, self-assessment and peer-review checklists can be developed to scaffold students' learning of argumentative writing. Similarly, such a framework can provide the criteria based on which rubrics for evaluating argumentative essays can be designed. As a comprehensive model, PoA will help teachers improve validity of their assessment by providing a comprehensive account of argumentative writing construct.